12.6k views
2 votes
-12 divided by 3 x (-8 + (-4) ^2 - 6) + 2

1 Answer

3 votes

Answer:

-3/2

Explanation:

Here we have an ambiguous notation. Hence, I assume you mean (-12/((3 x (-8+ (-4)^2 -6) +2), which is the one that makes more sense.

First, we work the arithmetic on the denominator (D).

D= 3 x (-8 + (-4)^2 - 6) + 2

D=3 x (-8 + (-4) x (-4) -6) + 2

D= 3x (-8 +16 -6) + 2

D= 3 x (2) + 2=6 + 2=8

Now, we just have to divide -12 by D to obtain the answer.

-12/D = -12/8 =(-2 x 2 x 3)/(2 x 2 x 2) = -3/2

User Dsounded
by
5.5k points